2009
DOI: 10.1021/ar900249x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bioinspired Mn4O4−Cubane Water Oxidation Catalysts: Lessons from Photosynthesis

Abstract: Hydrogen is the most promising fuel of the future owing to its carbon-free, high-energy content and potential to be efficiently converted into either electrical or thermal energy. The greatest technical barrier to accessing this renewable resource remains the inability to create inexpensive catalysts for the solar-driven oxidation of water. To date, the most efficient system that uses solar energy to oxidize water is the photosystem II water-oxidizing complex (PSII-WOC), which is found within naturally occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
383
0
4

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 527 publications
(395 citation statements)
references
References 54 publications
2
383
0
4
Order By: Relevance
“…Indeed, even the oxygen evolving complex of photosystem II experiences up to a ten-fold reduction in catalytic activity in vivo as opposed to in vitro. 340,341 In addition, Bard et al 350 have noted that the heterogeneous electrochemical rate constants for reactants bound in a surface layer are generally 2-3 orders of magnitude smaller than those for the same reactants in the solution phase. In light of this, a direct comparison between surface based and solution based catalysts seems unreasonable.…”
Section: Electrocatalytic Performance -Turnover Frequenciesmentioning
confidence: 99%
“…Indeed, even the oxygen evolving complex of photosystem II experiences up to a ten-fold reduction in catalytic activity in vivo as opposed to in vitro. 340,341 In addition, Bard et al 350 have noted that the heterogeneous electrochemical rate constants for reactants bound in a surface layer are generally 2-3 orders of magnitude smaller than those for the same reactants in the solution phase. In light of this, a direct comparison between surface based and solution based catalysts seems unreasonable.…”
Section: Electrocatalytic Performance -Turnover Frequenciesmentioning
confidence: 99%
“…[18,19] This dichotomy between the two crystal structures made it possible to test the bioinspired hypothesis. [20] The higher calcination temperature and longer reaction times used to form the layered polymorph gives rise to increasing crystallite size. [16] To reduce this difference in particle sizes, the authors adapted a sol-gel method [21] that forms nano-particles (50-100 nm) and limited particle size differences to only two-fold.…”
Section: Gerry Swiegers Is a Professor In The Intelligentmentioning
confidence: 99%
“…[38] While this is of interest in relation to the photosensitisation of the manganese cubanes that ACES researchers and their collaborators have developed, [20] we have rather focussed our attention on the development of porphyrin-based catalytic systems for water oxidation. In 1994, Naruta et al reported for the first time oxygen evolution by a four electron oxidation of water using a rigid ortho linked manganese porphyrin dimer.…”
Section: Porphyrins As Light Harvesters and Catalystsmentioning
confidence: 99%
“…Este processo é bem manipulado pela natureza e com boa eficiência, mas tem sido muito difícil reproduzir essa eficiência através da catálise homogênea artificial. 93 O armazenamento da energia solar através da fotossíntese é uma das mais notáveis façanhas da natureza. As tecnologias disponíveis exploram este processo para geração de energia processando partes da biomassa de plantas em etanol e biomassa de algas em biodiesel.…”
Section: A Fotossíntese Artificialunclassified